Innovative Technologies and Engineering Solutions for Ensuring the Earthquake Resistance of Buildings and Structures - Sirojiddin, Muradov (EDUMALSYS Journal of Research in Education Management, 2025)
This article analyzes innovative technologies and engineering solutions aimed at enhancing the earthquake resistance of buildings and structures. It discusses the advantages of seismic isolation, damping systems and dampers, advanced construction materials, 3D printing, and Building Information Modeling (BIM) in improving structural performance under seismic loads. Drawing on international practice, the article considers the prospects for introducing these technologies and solutions in Uzbekistan and highlights their potential contribution to increasing the resilience and safety of the built environment.